The Application Value of Syndecan-2 Gene Methylation for Colorectal Cancer Diagnosis: A Clinical Study and Meta-Analyses - Yue, Congbo; Zhang, Yaping; Wang, Yanlei; Zhang, Zhenhong; Zhang, Mengjiao; Wang, Huayang; Chen, Wendan; Shang, Ziqi; Xin, Yiwei; Zhang, Xin; Zhang, Yi (Frontiers in Medicine, 2022)
Objective: Syndecan-2 (SDC2) methylation has been previously reported as a sensitive biomarker for the early detection of colorectal cancer (CRC). ddPCR is the latest development of PCR technology. It can accurately detect and quantify the target sequence of nucleic acid. It is widely used in research and clinical diagnosis. In the present study, we aimed to develop a ddPCR method to detect SDC2 gene methylation and evaluate the diagnostic value of SDC2 gene methylation. Methods: Firstly, a ddPCR method was developed to measure SDC2 methylation in stool samples collected from 51 cases of normal, 23 cases of adenoma, and 86 cases of CRC. Subsequently, a meta-analysis of existing studies was conducted to judge the diagnostic value of SDC2 gene methylation in CRC. PUBMED, EMBASE, Web of Science, and Scopus databases were searched for relative studies. Meta-analysis was performed using Meta Disc 1.4 and STATA 15.0 software. Results: The ddPCR showed that the linearity, sensitivity, and specificity for the detection of SDC2 gene methylation could be down to 0.1% methylation level and 5 ng of methylated DNA input. In 109 cases of CRC, 107 cases could be detected, and the sensitivity was 98.17%. The median value of the percentage of methylated reference (PMR) in colorectal adenoma and CRC patients was significantly higher compared with the normal individuals (P < 0.001). We also found that the PMR value was associated with the clinical staging of CRC. The difference of PMR in stage II and stage IIIA was statistically significant (P<0.05). Moreover, the meta-analysis showed that 11 out of 87 studies were identified to report the feasibility of SDC2 gene methylation as a method to diagnose early CRC. The pooled sensitivity and specificity of SDC2 gene methylation test for CRC were 0.80 [95% CI (0.68-0.88)] and 0.93 [95% CI (0.91-0.94)], respectively. The pooled diagnostic odds ratio and area under curve were 52.46 [95% CI (30.43-90.45)] and 0.94 [95% CI (0.92, 0.96)], respectively. Conclusions: ddPCR method was more sensitive and convenient to detect SDC2 gene methylation, and the pooled analysis showed that methylated SDC2 was a valuable biomarker for the non-invasive detection of CRC.